Arthroscopic management of articular and peri-articular fractures of the upper limb. Issue 9 (September 2016) - Dei Giudici, Luca; Faini, Andrea; Garro, Luca; Tucciarone, Agostino; Gigante, Antonio
Abstract : The management of articular fractures is always a matter of concern. Each articular fracture is different from the other, whatever the classification system used and the surgical or non-surgical indications employed by the surgeon. The main goals remain anatomical reduction, stable fixation, loose body removal and minimal invasiveness. Open procedures are a compromise. Unfortunately, it is not always possible to meet every treatment goal perfectly, since associated lesions can pass unnoticed or delay treatment, and even in a 'best-case' scenario there can be complications in the long term. In the last few decades, arthroscopic joint surgery has undergone an exponential evolution, expanding its application in the trauma field with the development of arthroscopic and arthroscopically-assisted reduction and internal fixation (ARIF) techniques. The main advantages are an accurate diagnosis of the fracture and associated soft-tissue involvement, the potential for concomitant treatments, anatomical reduction and minimal invasiveness. ARIF techniques have been applied to treat fractures affecting several joints: shoulder, elbow, wrist, hip, knee and ankle. The purpose of this paper is to provide a review of the most recent literature concerning arthroscopic and arthroscopically-assisted reduction and internal fixation for articular and peri-articular fractures of the upper limb, to analyse the results and suggest the best clinical applications. ARIF is an approach with excellent results in treating upper-limb articular and peri-articular fractures; it can be used in every joint and allows treatment of both the bony structure and soft-tissues. Post-operative outcomes are generally good or excellent. While under some circumstances ARIF is better than a conventional approach, the results are still beneficial due to the consistent range of movement recovery and shorter rehabilitation time. The main limitation of this technique is the steep learning curve, but investing in ARIF reduces intra-operative morbidity, surgical errors, operative times and costs. Cite this article: Dei Giudici L, Faini A, Garro L, Tucciarone A, Gigante A. Arthroscopic management of articular and peri-articular fractures of the upper limb. EFORT Open Rev 2016;1:325-331. DOI: 10.1302/2058-5241.1.160016.